Age- and gender-based social inequalities in palliative care for cancer patients: a systematic literature review - Rodríguez-Gómez, Marina; Pastor-Moreno, Guadalupe; Ruiz-Pérez, Isabel; Escribà-Agüir, Vicenta; Benítez-Hidalgo, Vivian (Frontiers in Public Health, 2024)
Objectives: Cancer is a major public health problem worldwide, given its magnitude and growing burden, in addition to the repercussions on health and quality of life. Palliative care can play an important role improving quality of life and it is cost-effective, but some population groups may not benefit from it or benefit less based on age and gender inequalities. The aim of this systematic review was to To analyse the available evidence on age-and gender-based social inequalities in access to and use of palliative care in cancer patients.Methods: A systematic review was conducted following the PRISMA guidelines. An exhaustive literature research was performed in Pubmed, CINHAL and Embase until November 2022 and were not restricted by language or date of publication. Eligible studies were observational studies analysing the access and use of palliative care in cancer patients.Fifty-three studies were included in the review. Forty-five analysed age and 44 analysed gender inequalities in relation to use of and access to palliative care. Our results show that older people receive poorer quality of care, worst symptom control and less preferences for palliative care. In relation to gender, women have a greater preference for the use of palliative care and generally have more access to basic and specialized palliative care services and palliative care facilities.This review reveals difficulties for older persons and men for access to key elements of palliative care and highlights the need to tackle access barriers for the most vulnerable population